Maroons and Mi’kmaq in Nova Scotia, 1796-1800 - Chopra, Ruma (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2017)
Forcibly relocated by the Jamaican government, the Maroons of Trelawney Town, Jamaica, reached Halifax in July 1796. Lieutenant-Governor John Wentworth, former loyalist governor of New Hampshire, experimented with integrating and converting these 150 uprooted black families, refugees of war. His self-congratulatory benevolence created and extended the fractured relationships among black and Aboriginal communities in the region. This article helps demonstrate the limits of British paternalism and the far-reaching consequences of distinguishing people of African ancestry from Aboriginal people.